Predomination and New Genotypes of Enterocytozoon bieneusi in Captive Nonhuman Primates in Zoos in China: High Genetic Diversity and Zoonotic Significance - Karim, Md Robiul (PLoS One, 2015)
To appreciate the genetic diversity and zoonotic implications of Enterocytozoon bieneusi in nonhuman primates (NHPs) in zoos, we genotyped E. bieneusi in captive NHPs in seven zoos located at six major cities in China, using ribosomal internal transcribed spacer (ITS)-based PCR and sequence analyses. A total of 496 fecal specimens from 36 NHP species under nine families were analyzed and E. bieneusi was detected in 148 (29.8%) specimens of 25 NHP species from six families, including Cercopithecidae (28.7%), Cebidae (38.0%), Aotidae (75.0%), Lemuridae (26.0%), Hylobatidae (50.0%) and Hominidae (16.2%) (P = 0.0605). The infection rates were 29.0%, 15.2%, 18.2%, 37.3%, 29.2%, 37.7% and 44.8% in Shijiazhuang Zoo, Wuhan Zoo, Taiyuan Zoo, Changsha Wild Animal Zoo, Beijing Zoo, Shanghai Zoo and Shanghai Wild Animal Park, respectively (P = 0.0146). A total of 25 ITS genotypes were found: 14 known (D, O, EbpC, EbpA, Type IV, Henan-IV, BEB6, BEB4, Peru8, PigEBITS5, EbpD, CM1, CM4 and CS-1) and 11 new (CM8 to CM18). Genotype D was the most prevalent one (40/148), followed by CM4 (20/148), CM1 (15/148), O (13/148), CM16 (13/148), EbpC (11/148). Of them, genotypes D, EbpC, CM4 and O were widely distributed in NHPs (seen in 9 to 12 species) whereas genotypes CM1 and CM16 were restricted to one to three NHP species. In phylogenetic analysis, 20 genotypes (121/148, 81.8%), excluding genotypes BEB4, BEB6, CM9, CM4 and CM18, belonged to group 1 with zoonotic potential. New genotype CM9 clustered in group 2 with BEB4 and BEB6. The remaining two genotypes CM4 and CM18 formed new cluster (group 9) in between two other genotypic clusters found in primates. The findings of high diversity in E. bieneusi genotypes and their zoonotic potentiality concluded the importance of captive NHPs as reservoir hosts for human microsporidiosis.